New related-key rectangle attack on 42-round SHACAL-2 - WEI Yong-zhuang1; 2 (Tongxin xuebao)
A new 34-round related-key rectangle distinguisher was constructed by exploiting the properties of the round transform of SHACAL-2. Moreover, two new relate-key rectangle attacks on 40-round and 42-round reduced SHACAL-2 were presented by using both the distinguisher and a technique of key-byte guessing. It is shown that related-key rectan- gle attacks with only 2 related keys on 40-round and 42-round reduced SHACAL-2 all require data complexity of about 2235 chosen plaintexts and time complexity of about 2432.6 encryptions on 40-round reduced SHACAL-2, and 2472.6 en- cryptions on 42-round reduced SHACAL-2, respectively. The presented results are better than previous published crypt- analytic results on reduced SHACAL-2 in terms of both the data complexity and the time complexity.